O14.1 Is an automated online clinical care pathway for people with genital chlamydia (chlamydia-occp) within an esexual health clinic feasible and acceptable? proof of concept study. (13th September 2015) - Estcourt, CS; Gibbs, J; Sutcliffe, LJ; Gkatzidou, V; Tickle, L; Hone, K; Aicken, C; Lowndes, C; Harding-Esch, E; Eaton, S; Oakeshott, P; Szczepura, A; et al.
Abstract : Introduction: UK health strategy supports self- and internet-based care. Within the eSTI 2 consortium (www.esti2.org.uk ) we developed UK's first automated Online Clinical Care Pathway for people with genital chlamydia (Chlamydia-OCCP) within an eSexual Health Clinic (eSHC). Chlamydia-OCCP includes: STI results service; clinical consultation; electronic prescription via community pharmacy; partner notification (PN); with integral telephone helpline support. It complies with regulatory, professional, prescribing and surveillance requirements. We report on a study to assess Chlamydia-OCCP feasibility and acceptability as an alternative to routine care. Methods: Non-randomised, exploratory study to evaluate Chlamydia-OCCP: 21.07.14 -13.03.15. Participants: 1) chlamydia-positive untreated Genitourinary Medicine (GUM) clinic attenders; 2) people testing chlamydia-positive and negative through six National Chlamydia Screening Programme (NCSP) areas' online postal self-sampling service. Exclusions: under 16 yrs; co-existing STIs, extra-genital chlamydia. Intervention: eligible people were sent an SMS message with a link to access results from eSHC via a password protected web-app, optimised for smartphone use. Having consented online chlamydia-positive users followed the automated Chlamydia-OCCP. Patients who declined received routine care. Evaluation: treatment rate; time to treatment; PN outcomes; engagement with clinical helpline and health promotion; safety; acceptability, costs. Results: GUM: of 197 eligible patients, 161 accessed results online, 112 consented, 110/112 (98%) treated (72 exclusively via Chlamydia-OCCP, median 1 day). NCSP: of 145 eligible patients, 133 accessed results online, 104 consented, 92/104 (88%) treated (59 exclusively via Chlamydia-OCCP, median 1 day). 28/515 sexual partners were managed solely online. 1176/1936, (61%) NCSP chlamydia-negative people accessed results online, of whom 407 accessed online health promotion. All patients who didn't access results online were managed routinely. Patients moved effectively between online, telephone and clinic-based care. Conclusion: Chlamydia-OCCP is a feasible, acceptable, safe alternative to routine care for management of people with genital chlamydia. Preliminary evidence indicates comparable treatment outcomes. If linked to home testing, Chlamydia-OCCP offers potential for wholly remote care. Disclosure of interest statement: Nothing to declare.